Proteostasis in the Male and Female Germline: A New Outlook on the Maintenance of Reproductive Health - Cafe, Shenae L.; Nixon, Brett; Ecroyd, Heath; Martin, Jacinta H.; Skerrett-Byrne, David A.; Bromfield, Elizabeth G. (Frontiers in Cell and Developmental Biology, 2021)
For fully differentiated, long lived cells the maintenance of protein homeostasis (proteostasis) becomes a crucial determinant of cellular function and viability. Neurons are the most well-known example of this phenomenon where the majority of these cells must survive the entire course of life. However, male and female germ cells are also uniquely dependent on the maintenance of proteostasis to achieve successful fertilisation. Oocytes, also long-lived cells, are subjected to prolonged periods of arrest during which they accrue and store mRNAs in the absence of transcription to support subsequent embryogenesis. Conversely, sperm cells, while relatively ephemeral, are completely reliant on proteostasis due to the absence of both transcription and translation. Despite these remarkable, cell-specific features there has been little focus on understanding protein homeostasis in reproductive cells and how/whether proteostasis is ‘reset’ during embryogenesis. Here, we seek to capture the momentum of this growing field by highlighting novel findings regarding germline proteostasis and how this knowledge can be used to promote reproductive health. In this review we capture proteostasis in the context of both somatic cell and germline ageing and discuss the influence of oxidative stress on protein function. In particular, we highlight the contributions of proteostasis changes to oocyte ageing and encourage a focus in this area that may compliment the extensive analyses of DNA damage and aneuploidy that have long occupied the oocyte ageing field. Moreover, we discuss the influence of common non-enzymatic protein modifications on the stability of proteins in the male germline, how these changes affect sperm function, and how they may be prevented to preserve fertility. Through this review we aim to bring to light a new trajectory for our field and highlight the potential to harness the germ cell’s innate proteostasis mechanisms to improve reproductive health. This manuscript will be of interest to those in the fields of proteostasis, ageing, male and female gamete reproductive biology, embryogenesis and life course health.